RANCANG BANGUN SISTEM DETEKSI KESUBURAN TANAH BERBASIS LED, KAMERA DAN DEEP LEARNING - Najib, M Faruq; Rakhmadi, Frida Agung (Sunan Kalijaga Journal of Physics, 2021)
This research is motivated by the lack of an effective and efficient soil fertility detection system. This study aimed to design and manufacture a soil fertility detection system based on LED, camera, and deep learning. This research was conducted in two stages, namely designing and manufacturing the soil fertility detection system. Design of the tool was carried out using Paint 3D software. Manufacturing of this detection system through 3 processes, namely manufacturing hardware, taking datasets, and making software